Factors Related The Job Satisfaction Among Migrant Nurses In Qatar - Uddin, Saiful (South East Asia Nursing Research, 2019)
Indonesian nurses migrated out of the country with various motifs, for instance, to earn a better income, enhancing the experience, personal development, and improvement of nursing ability. The phenomenon where nurses turn over from their job can also be caused by job dissatisfaction. Nurses job’s satisfaction needs serious attention since the nurses are spearheading the implementation of services. The objective of this study to get an idea of the level of job satisfaction and to identify factors affecting job satisfaction in Indonesian migrants nurse in Qatar. The research method is a descriptive analytic using cross-sectional approach. The research’s sample represents a total sample of 39 Indonesian nurses who work in an outpatient clinic in Qatar in February 2012. The results showed that Indonesian migrant nurses working in Qatar are satisfied with the work of 51.3%. The results of the analysis showed no correlation between length of service and working time arrangements with job satisfaction, whereas there was no correlation between age, education degree and family status with job satisfaction. The recommendations can be given to health care management in Qatar are to further improve the promotion system and nurses self-development and to increase incentives for nurses who do shift duty. Nurses are advised to increase the level of education and improve the performance of work.